Chương trình 135 phát triển kinh tế -xã hội các xã đặc biệt khó khăn vùng dân tộc và Miền núi giai đoạn 1(1998-2000) - Dung, Hoàng Công (Nhà xuất bản nông nghiệp, 2016)
The Prime Minister issued Decision No. 135 on 31st July 1998 in order to improve the material and spiritual life of the people in extremely difficult upland communes and distant and remote areas, to help local people out of poverty and backward, under-developed status, and to guarantee social security and national defense. The program was implemented at 1,200 communes in 1999 and 1,878 extremely difficult and border communes. The Government has mobilized various financial sources for investment in these communes. Such investment from the Central State Budget in 1999 was 508 billion VND and 700 billion VND in 2000. In these two years, 169 billion VND from provincial budgets was also invested in the program. Local ethnic people contribution to this program in the form of labor was equivalent to approximately 150 billion VND. Ministries, branches, organizations, better-off provinces and cities and corporations 91 also provided assistance equal to 134 billion VND to extremely difficult communes. The total fund mobilized for the program from various sources plus the integrated capital from other programs and projects for the communes under the 135 program of ministries, branches and localities was over 700 billion VND in 1999 (508 billion VND from the Central Budget) and over 1,200 billion VND in 2000 (700 billion VND from the Central Budget). On average, each of the communes was invested 700 million VND per year from the program, of which 400 million VND was from the Central Budget. Result of the program in the first two years: 4,867 infrastructure works have been completed and used. These works include roads, small irrigation systems, fresh water supply, electricity, schools, health clinics and markets... - Construction of commune group centers: the policy to establish commune group centers was issued in under Decision 35/TTg. Over the last 5 years, with the investment capital from the State Budget of 520 billion VND (204 billion from the Central Budget and 316 billion VND from local budgets), 330 commune group centers have been built. As at the end of the year 2000, 75 commune group centers were basically completed, of which 16 centers had all works completed. - Residential area planning: Various projects, programs and the infrastructure construction part in the 135 program have been combined to rearrange residential areas. Up to the end of 2000, the Ministry of Defense has rearranged 50,000 households according to residential area planning in border areas to help them stabilize their life and production. It has also planned for 100,000 households to come and live in fallow land in border areas and marine islands by 2005. After 2 years of implementation, the 135 program has contributed to the re-arrangement of about 120,000 households in the necessary areas of the program. 310 - The program has also implemented many measures to develop forestry and agriculture as well as processing and consumption of products from mountainous region. In addition, it has trained cadres of hamlet and villages. The percentage of poor and hungry households in extremely difficult communes in many provinces has declined by over 5% per year thanks to the 135 program. A number of provinces has already achieved this objective of the period of 2000 - 2005. However, there are certain shortcomings in the implementation process: Not enough resources have been mobilized for the program The current mechanism has not been compatible to the implementation process The progress of construction work for the last two years has been very slow Democracy and openness have not promoted in some localities or have only been done formally; all construction works were given to contractors while there are works which can be done by local people, leaving negative impacts. Certain districts have many works on large areas, and being unable to manage and supervise them, the district authorities left them all to contractors, resulting in loss of materials and low quality construction works. Commissioned works in certain areas have not been well used and managed. Some localities have not been active in seeking solutions to improve production and stabilize the living conditions of their inhabitants.